The Carnegie Foundation for the Advancement of Teaching Division of Educational Enquiry and the Shaping of Canadian Higher Education - Lang, Daniel W. (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2022)
When the Carnegie Foundation for the Advancement of Teaching was established in 1905, universities in Canada and New-foundland were eligible for participation in a pension fund for faculty and grants to universities. Canadian universities were quick to seek access to the Carnegie pension plan and for support from the Corporation. Access to both programs came with strings attached, including recommendations of educational studies commissioned by the Foundation, six of which addressed Canadian higher education specifically. As attractive as the prospect of Carnegie support was, it posed a dilemma for many universities and self-regulated professions associated with them in regard of mandate and autonomy. This study investigates how Canadian universities and the professional societies associated with them responded to the studies, found ways to take advantage of the reports, or in some cases make compromises to manage the internal conflicts that arose from them, and finally their embryonic introduction of the concept planned systems of higher education.